Pengaruh Rasio Profitabilitas terhadap Nilai Perusahaan (Studi pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Nurfitriani, Ika (CV. Kalimasada Group, 2023)
This research aims to analyze the effect of profitability ratios on company value in LQ45 companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The profitability ratios used in this research include Return on Assets (ROA) and Return on Equity (ROE). Company value is measured using Price to Book Value (PBV). The research method used is quantitative research. Data was obtained from the LQ45 company's annual financial report published during that period. The research results show that profitability ratios have a significant influence on company value. In particular, ROA and ROE have a positive and significant influence. This research has the implication that company management needs to pay attention to profitability ratios as an important indicator in increasing company value. Apart from that, investors can use profitability ratios as a consideration in making investment decisions.